Kajian Sistematik : Hubungan Kemampuan Berpikir Aljabar dan Resiliensi Matematis pada Pembelajaran Matematika - Adjeng Alifiahaqsya, Retno; Sadieda, Lisanul Uswah; Lailiyah, Siti (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study aims to examine the relationship between algebraic thinking skills and mathematical resilience in mathematics learning using the Systematic Literature Review (SLR) method. This method is employed to analyze and synthesize findings from various relevant studies on these two aspects. A total of 20 articles meeting the inclusion criteria were reviewed, focusing on topics related to algebraic thinking skills and mathematical resilience in mathematics learning. The findings indicate a positive relationship between algebraic thinking skills and mathematical resilience, showing that students with strong algebraic skills are better equipped to face challenges in mathematics. These findings highlight the importance of effective algebra instruction in enhancing students' mental resilience when encountering difficulties in mathematics learning.